2018
DOI: 10.1108/jacpr-09-2016-0253
|View full text |Cite
|
Sign up to set email alerts
|

Understanding revenge pornography: public perceptions of revenge pornography and victim blaming

Abstract: Journal of Aggression, Conflict and Peace Research 2 AbstractPurpose: The disclosure of private images with the intent of causing distress is often described as 'revenge pornography'. In the UK, this newly legislated crime has received a high level of media attention following several high profile cases, however there is a paucity of research in this area.Methods: 168 adults (UK general public) completed an online survey using a vignette approach. Views of the influence of perpetrator-victim relationship lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 17 publications
3
37
0
Order By: Relevance
“…The results strengthen previous reports of victim-blaming in cases of NCII (Bothamley and Tully, 2018;Scott and Gavin, 2018) and add to the limited body of evidence on law enforcement victim-blaming. As NCII is a form of sexual violence, the results can be interpreted within the framework of gendered stereotypical thinking, similar to the one seen toward victims of rape.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results strengthen previous reports of victim-blaming in cases of NCII (Bothamley and Tully, 2018;Scott and Gavin, 2018) and add to the limited body of evidence on law enforcement victim-blaming. As NCII is a form of sexual violence, the results can be interpreted within the framework of gendered stereotypical thinking, similar to the one seen toward victims of rape.…”
Section: Discussionsupporting
confidence: 86%
“…Media coverage of high-profile cases has also contributed to increased awareness of the problem (e.g., famous Hollywood actresses whose intimate photos were stolen and disseminated, local cases of large-scale dissemination of intimate materials of anonymous women, or cases involving local celebrities). Yet, being a relatively new phenomenon, only a few studies have addressed the issue of perceptions of NCII (Bothamley and Tully, 2018;Scott and Gavin, 2018;Zvi and Shechory-Bitton, 2020). To our knowledge, only one study has addressed the issue of police officers, examining 783 UK police officers and their knowledge of and experience with NCII cases (Bond and Tyrrell, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research into public perceptions of revenge pornography in the UK found sex differences in victim blaming, with men being significantly more likely to do this than women (Bothamley & Tully, 2018). This is consistent with victim blaming in relation to a range of sexual offences (McCaul, Veltum, Boyechko, & Crawford, 1990).…”
Section: Intrasexual Competition As a Predictor Of Women's Judgementssupporting
confidence: 58%
“…Each item is rated using a scale anchored from "Not at all/Very unlikely" to "Definitely/Very likely". Whereas Bothamley and Tully's (2018) original vignettes framed the mode of image dissemination as posting images online, we instead framed the act of revenge pornography as distributing images amongst a friendship group. The rationale for this was to avoid potential ceiling effects of participant responses.…”
Section: Judgements Of Revenge Pornography (Jrp; Bothamley and Tully 2mentioning
confidence: 99%
“…Two recent revenge pornography scenario studies have examined the relationship between numerous extra-legal factors and perceptions of revenge pornography. Bothamley and Tully (2018) found that, compared to women, men were more likely to blame the victim, and to perceive the situation as less serious in terms of the need for police intervention and potential mental harm to the victim. Extending this, Scott and Gavin (2018) report that these sex differences in perceptions of seriousness occur only in cases involving a male perpetrator and a female victim.…”
Section: Introductionmentioning
confidence: 95%